2020
DOI: 10.21037/tau.2020.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Is dynamic contrast enhancement still necessary in multiparametric magnetic resonance for diagnosis of prostate cancer: a systematic review and meta-analysis

Abstract: Background: The purpose of this study is to systematically review the literatures assessing the value of dynamic contrast enhancement (DCE) in the multiparametric magnetic resonance imaging (mpMRI) for the diagnosis of prostate cancer (PCa).Methods: We searched Embase, PubMed and Web of science until January 2019 to extract articles exploring the possibilities whether the pre-biopsy biparametric magnetic resonance imaging (bpMRI) can replace the position of mpMRI in the diagnosis of PCa. The sensitivity and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
(206 reference statements)
0
12
0
Order By: Relevance
“…Rosenkrantz et al found that T2WI combined with DWI had higher sensitivity than T2WI alone, but the addition of DCE did not improve the diagnostic sensitivity (36). A meta-analysis reported that bpMRI was only 7% less sensitive than mpMRI in the diagnosis of PCa (37). In another meta-analysis, Woo et al found that the performance of bpMRI was similar to that of mpMRI in the diagnosis of PCa (38).…”
Section: Discussionmentioning
confidence: 99%
“…Rosenkrantz et al found that T2WI combined with DWI had higher sensitivity than T2WI alone, but the addition of DCE did not improve the diagnostic sensitivity (36). A meta-analysis reported that bpMRI was only 7% less sensitive than mpMRI in the diagnosis of PCa (37). In another meta-analysis, Woo et al found that the performance of bpMRI was similar to that of mpMRI in the diagnosis of PCa (38).…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have investigated the power of the simplified bpMRI protocol, especially in terms of its diagnostic efficiency in PCa. A recent meta-analysis (12) assessed whether the prebiopsy bpMRI could replace mpMRI in the diagnosis of PCa and showed that the pooled specificity demonstrated little difference between bpMRI and mpMRI, but the sensitivity indicated a significant difference. Another two meta-analyses carried out by Alabousi They both proved that the pooled summary statistics demonstrated no significant difference in sensitivity or specificity between bpMRI and mpMRI.…”
Section: Discussionmentioning
confidence: 99%
“…High accuracy of unenhanced prostate MRI, combined with PSA evaluation, was shown for the detection of clinically significant PCa [ 8 , 12 , 21 , 22 ], and a meta-analysis showed that bpMRI, with a high b-value, is a sensitive tool for diagnosing PCa [ 23 ]. We considered previous studies, both those in favor of the added value of DCE [ 24 , 25 ] and those against it [ 21 , 26 ], arguing that different results may have been caused by heterogeneity in technical issues, study populations, and interpretation criteria.…”
Section: Discussionmentioning
confidence: 99%